The Longitudinal Impact of the SARS-CoV-2 Pandemic on Participants From the Boston Puerto Rican Health Study - Kelsey M. Mangano, PhD, RD; Liam E. Fouhy, MPH; Xiyuan Zhang, MPH; Sabrina E. Noel, PhD; Serena Rajabiun, PhD; Lisa C. Merrill, MS, MPH; Luis M. Falcon, PhD; Katherine L. Tucker, PhD (Elsevier, 2023)
Introduction: The aim of this study was to investigate the impact of the SARS-CoV-2 pandemic on older Hispanic adults. Methods: A total of 522 participants (or their family members, if deceased) from the Boston Puerto Rican Health Study were asked whether they had been diagnosed with SARS-CoV-2, across 2 survey phases. In Phase 1 (May 2020-August 2020, N=497), participants answered survey questions related to SARS-CoV-2 exposure, diagnosis, and transmission and 5 family members reported deaths. In Phase 2, participants were again surveyed (January 2021-June 2021; n=420, and 2 family members reported deaths). SARS-CoV-2 diagnosis and/or death apparently from SARS-CoV-2 was self-reported. Results: In 2020, 5.2% reported that they had been SARS-CoV-2 positive; by June 2021, a cumulative 11.0% reported having been SARS-CoV-2 positive (including cases and deaths in the first survey). A total of 7 participants (1.3%) reportedly died of SARS-CoV-2. Language acculturation was significantly lower among participants with SARS-CoV-2 (13.7±17.9) than among those without SARS-CoV-2 (20.0±21.4; p=0.049). The mean length of return to usual health was 28±38 days (range=0-210 days; median=15 days). Depressive symptomatology was significantly lower during the pandemic (Center for Epidemiologic Studies Depression Scale score: 13.4±11.6) than in the same participants before the pandemic (17.8±11.7; p=0.001). A total of 32% (n=135) of participants reported greater communication with friends and family than in the months before the pandemic, and 41% (n=172) reported no change. Conclusions: Public health models should be personalized to communities, considering their unique structures and cultural beliefs. Social resiliency may be key for future programmatic responses to pandemics to reduce the mental health burden.